Conceptual understanding of Sustainable Health and Linking Nutrition to Sustainable Development Goals - Juneja, Khushboo; Sinha, Ratnesh (Indian Journal of Community Health, 2023)
Nutrition is a development indicator. It indicates advancement in health, education, employment, women’s empowerment, poverty, inequality reduction, and it can help in building peaceful, secure, and stable societies.” It is one of the important components which is directly or indirectly related to Sustainable Development Goals (SDGs). Multiple factors such as education, economic status, occupation, water, sanitation, hygiene, etc are interlinked with nutrition. In this article, we have emphasized the relationship of various SDGs with nutrition. Global and multi-sectorial involvement is required in the battle with malnutrition. Adequately nourished people are more productive and active. By breaking the cycles of hunger and malnutrition, we can create a path for achieving SDGs.